The Identifying Students’ Misconceptions in IUPAC Nomenclature of Organic Compounds in Public Senior Secondary Schools in Ibadan, Nigeria - Olasunkanmi OGUNDIJI (MASI Mandiri Edukasi, 2025)
The ability to accurately name organic compounds according to IUPAC rules is fundamental in chemistry education. Nevertheless, recent studies indicate students’ misconceptions in this regard. A qualitative research design involving 56 respondents was employed. The instruments for the study are the Students’ Perception Scale in IUPAC Nomenclature (r = 0.80) and the IUPAC Nomenclature Diagnostic Test (r = 0.71). The result showed mixed perceptions of students in this regard. Among the identified students' misconceptions in naming organic compounds are poor knowledge of the parent chain, inability to make sense of substituents, functional groups, isomerism, alkyl groups, etc. Students’ misconceptions in this regard could have a negative implication on their achievement. The teacher could identify and address those misconceptions through innovative strategies and regular feedback. Diagnosing such difficulties would help educators and policymakers work together to develop targeted support systems, improve teaching methods, and promote student success in chemistry.